PENGARUH UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING - Esa Martawati; Samin Samin (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study aims to examines the effect of firm size and institutional ownership on company performance with debt policy as intervening variable in consumer goods company listed on the Indonesian Stock Exchange. The sample of this research amount 25 consumer goods company listed on the Indonesian Stock Exchange during the period 2008-2011 that were selected by using purposive sampling method. The data used are secondary data from financial statements published by the Indonesian Stock Exchange. The analysis technique used here is path analysis. The result of the research show firm size and institutional ownership simultaneously significant effect on debt policy. Partially, firm size has no significant effect on debt policy, while institutional ownership has a significant effect on debt policy. In addition, firm size, institutional ownership, and debt policy simultaneously significant effect on company performance. Partially, firm size and institutional ownership has a significant effect on company performance, whereas no significant effect on company performance is debt policy. There is not indirect effect between firm size and institutional ownership on company performance through debt policy as intervening variable.